Peningkatan Keterampilan Motorik Halus Melalui Kegiatan Membatik - Winarsih Winarsih (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
The purpose of this study to describe the process and learning outcomes through the implementation of batik activities that can improve fine motor skills of children in group A kindergarten Aisyiyah Bustaanul Athfaal Ciracas, East Jakarta, Year 2015/2016. The subjects of this study were 10 children. The research method used is based upon the model of action research which consists of four phases, including planning, action, observation and reflection. The study consisted of two cycles where each cycle consists of eight meetings. Data analysis techniques used in this research is the analysis of qualitative and quantitative data. Analysis of qualitative data by data reduction, data display and data verification. Quantitative data analysis with descriptive statistics that compare the results obtained from pre-action, the first cycle and the second cycle. The results of this study showed an increased fine motor skills through activities batik, can be proved by the average level of performance development (TCP) fine motor skills of children in pre-action amounted to 21 increased in the first cycle and the second cycle to 34 to 44.Keywords: Fine motor skills, batik activities, early childhoodDOI: http://dx.doi.org/10.23960/jiip.v1i1.18010